PELATIHAN DAN PEMBINAAN BAGI PENGUSAHA KECIL MIKRO DIBIDANG PARIWISATA DI KAWASAN PESISIR PANTAI CEMARA LEMBAR KABUPATEN LOMBOK BARAT - Masrun; Akhmad Jufri; Titi Yuniarti; M. Firmansyah (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2022)
This training carried out a manifestation of the implementation of the Tridharma of Higher Education in the form of community service, the theme is "Training and Development of Entrepreneurship of based on local potential in cultivation for Tourism in Coastal Areas of Cemara Lembar, West Lombok Regency." The purpose of this research is to train micro-small entrepreneurs which includes: build a motivation in business, increase market access and prepare the small business community to adapt the uncertain environment. The method used in this training: speech to convey materials, question and answer, participants will be fostered by the community service implementation team. According to the observation during the training, almost all participants who attend the training gave a positive (good) responses to the training materials. Through training and coaching, participants show increasing knowledge, even though insignificant from the conditions before. Based on the results concluded that the important thing is the participants in this training are expected to be followed up with assistance, apprenticeship and comparative studies at successful entrepreneurs / companies